Biomarkers of related driver genes predict anti-tumor efficacy of immune checkpoint inhibitors - Jiang, Shuai; Geng, Shuai; Luo, Xinyu; Zhang, Can; Yu, Yang; Cheng, Mengfei; Zhang, Shuo; Shi, Ning; Dong, Mei (Frontiers in Immunology, 2022)
Cancer is a disease with high morbidity and mortality in the world. In the past, the main treatment methods for cancer patients were surgery, radiotherapy and chemotherapy. However, with early treatment, the recurrence rate of cancer is higher, and the drug resistance of cancer cells is faster. In recent years, with the discovery of immune escape mechanism of cancer cells, Immunotherapy, especially Immune Checkpoint Inhibitors (ICIs), has made a breakthrough in the treatment of solid tumors, significantly prolonging the overall survival time and disease-free progression in some solid tumors, and its clinical benefits are more prominent than those of traditional anti-tumor drugs, which has become the hope of cancer patients after the failure of multi-line therapy. Immune checkpoint inhibitors mainly include antibodies targeting cytotoxic T lymphocyte antigen-4 and antibodies targeting programmed cell death receptor-1 and its ligand. At present, many immune checkpoint inhibitors are used widely, but there are still some problems to be solved, such as the lack of effective biomarkers to predict clinical efficacy. This review systematically summarizes the biomarkers that may affect the clinical benefits of immune checkpoint inhibitors, and provides accurate scientific basis for clinical practice.